The Role of Emotional and Spiritual Intelligence in Students’ Physics Learning Achievement - Elky Fahrianor; Abdul Salam; Sarah Miriam (Universitas Lambung Mangkurat, 2026)
This study aims to examine the extent to which emotional intelligence and spiritual intelligence influence students’ physics learning outcomes at the senior high school level. A quantitative approach with a correlational design was employed. The population comprised 124 twelfth-grade students from a public senior high school in Banjarmasin, Indonesia, with a sample of 60 students selected through purposive sampling. Data on emotional and spiritual intelligence were collected using structured questionnaires, while physics learning outcomes were obtained from students’ first-semester report card grades for the 2024/2025 academic year. Multiple linear regression analysis was conducted using SPSS version 22. The findings indicate that emotional intelligence and spiritual intelligence simultaneously exert a statistically significant effect on physics learning outcomes (F = 12.831; p < 0.05). The coefficient of determination (R² = 0.310) suggests that both variables account for 31% of the variance in students’ physics achievement. Partially, emotional intelligence demonstrates a stronger contribution (β = 0.390; p = 0.002) compared to spiritual intelligence (β = 0.262; p = 0.036). These results highlight the meaningful role of non-cognitive factors, particularly emotional intelligence, in supporting academic achievement in physics. The study provides empirical support for considering emotional and spiritual dimensions as complementary factors in physics instruction, while acknowledging the methodological and sampling limitations inherent in the research design.